Multisegmental motor activity in the segmentally restricted gin trap behavior in Manduca sexta pupae - Lemon, William C.; Levine, Richard B. (Journal of Comparative Physiology A: Neuroethology, Sensory, Neural, and Behavioral Physiology, 1997)
Stimulation of sensory neurons innervating hairs in the gin traps on the abdomen of Manduca sexta pupae evokes a rapid bending of the abdomen that is restricted to one or more of the three articulating posterior segments. However, electrical stimulation of the gin trap sensory nerve in an isolated abdominal nerve cord evokes characteristic motor neuron activity in every abdominal segment. To determine if the segmentally distributed motor activity also occurred in intact animals and how it contributed to the segmentally restricted reflex movement, mechanical stimulation of the sensory hairs in intact animals was used to evoke reflex responses that were recorded as electromyograms synchronized with video recordings of the behavior. Motor activity was monitored during movements to determine if there was activity in many segments when the movement was restricted to one segment. Coordinated muscle activity was evoked throughout the abdomen in response to stimulation of any of the three gin traps, even when movement was restricted to one segment. Differences in the timing of ipsilateral and contralateral motor activity among segments allowed the closing of gin traps to be segmentally restricted. These findings suggest that the neural circuit underlying the gin trap reflex is distributed throughout the abdominal nerve cord. This network generates a complex, yet coordinated, motor pattern with muscular activity in many abdominal segments that produces a localized bending reflex.